Bringing Traditional Arts in Teaching English for Visual Art Students in Indonesia - Anisa Putri Cahyani (Proceedings International Conference on Teaching and Education (ICoTE), 2022)
Traditional arts and culture, as a part of national identity, can be both purpose and means of teaching and learning English, especially for visual art students in higher education. This study captures how traditional arts are brought into English classrooms at Indonesian Institute of Arts Surakarta. Data are collected through observation, interview, and group discussion, and are analyzed qualitatively, by the techniques of data organizing, coding, interpreting, displaying and concluding. The findings show that Indonesian traditional arts are included in the topics of materials, classroom tasks, and assignments of English teaching and learning. However, the implementation is adjusted following each major or study program. Generally, the forms of arts are related to traditional culture products, either artifacts or non-artifact, such as Batik (including the making process and the ornaments), Keris, and Cultural Activities. Such incorporation of art and language leads to the communicative atmosphere of art creation and appreciation.